Operational excellence through CRISIL rating during COVID-19 pandemic of a foreign bank in Bangladesh: A case of Commercial Bank of Ceylon PLC - Ghosh, Milisha (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.